Prevention of terrorism from TADA to POTA - Varma, Adarsh Kumar; Jethmalani, Ram(fwd) (New Delhi, 2003)
There was a furore when the Prevention of Terrorism Bill (POTA) was passed on March 26, 2002, by joint session of the two houses of Parliament. Leader of the Opposition Sonia Gandhi said that it was being "bulldozed" with the aim of "subverting the spirit of the Constitution". But TADA, the predecessor of POTA, became law in 1985 when the Congress was in power. This book seeks to remind readers of all this and traces how India and the world woke up to the need for a law to prevent terrorism.
Keywords: Terrorism